Impaired instrumental learning in Spred1−/− mice, a model for a rare RASopathy. (4th March 2021) - Borrie, Sarah C.; Horner, Alexa E.; Yoshimura, Akihiko; Legius, Eric; Kopanitsa, Maksym V.; Brems, Hilde
Abstract: RASopathies are neuro‐cardio‐facio‐cutaneous disorders stemming from mutations in genes regulating the RAS‐MAPK pathway. Legius syndrome is a rare RASopathy disorder caused by mutations in the SPRED1 gene. SPRED1 protein negatively regulates activation of Ras by inhibiting RAS/RAF and by its interaction with neurofibromin, a Ras GTPase‐activating protein (RAS‐GAP). Cognitive impairments have been reported in Legius syndrome as well as in other RASopathy disorders. Modelling these cognitive deficits in a Spred1 mouse model for Legius syndrome has demonstrated spatial learning and memory deficits, but other cognitive domains remained unexplored. Here, we attempted to utilize a cognitive touchscreen battery to investigate if Spred1 −/− mice exhibit deficits in other cognitive domains. We show that Spred1 −/− mice had heterogeneous performance in instrumental operant learning, with a large subgroup ( n  = 9/20) failing to reach the standard criterion on touchscreen operant pretraining, precluding further cognitive testing. To examine whether targeting the RAS‐MAPK signalling pathway could rescue these cognitive impairments, Spred1 −/− mice were acutely treated with the clinically relevant mitogen‐activated protein kinase (MEK) inhibitor PD325901. However, MEK inhibition did not improve their instrumental learning. We conclude that Spred1 −/− mice can model severe cognitive impairments that cannot be reversed in adulthood. Abstract : Spred1 −/− mice, a mouse model for a rare RASopathy disorder, are impaired in touchscreen‐based instrumental learning.